Between Fear and the Law: A Psychological Study of Domestic Violence Survivors in Family Law Proceedings - Toha Ma'arif (Bulletin of Counseling and Psychotherapy, 2025)
This article examines a fundamental problem in family law practice that remains dominated by normative– procedural approaches and assumptions of legal rationality, resulting in insufficient sensitivity to the psychological conditions of survivors of domestic violence (DV). The central issue addressed is how trauma, fear, and unequal power relations influence survivors’ legal behavior and decision-making within family court proceedings. This study aims to integrate perspectives from trauma psychology into family law analysis in order to develop a more contextualized and justice-oriented understanding of survivors’ legal conduct. The research employs a qualitative method with a normative–conceptual and analytical design, drawing on statutory regulations, Islamic family law, court decisions, and a systematic review of literature in trauma psychology and legal psychology. The findings demonstrate that survivors’ legal behaviors—often perceived as ambivalent, hesitant, or inconsistent—can be rationally explained through the frameworks of trauma bonding, fear conditioning, and coping mechanisms. These results highlight that the failure of legal systems to account for trauma dynamics risks reproducing bias, retraumatization, and substantive injustice. Accordingly, this study recommends the development of a trauma-informed family law psychology model as a foundation for reforming family court practices toward a more empathetic and survivor- responsive justice system.